The Bear Grylls Adventure. Book 10, The Mountain Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2020)
The tenth in the fun new 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS. A mysterious compass with a fifth direction transports a young girl to a mountain top high above sea level, where the air is thin, the steep drops are treacherous and the conditions tough.